Fluid-structure interaction (fsi) modelling in reed valves - Liu, XingChen (2014)
Reed valves have been in use for thousands of years in the past. It is still being used in modern designs for example in revolving compressors. Past attempts to study reed valves were difficult due to the complex nature of solving 2-way Fluid Solid Interactions with analytical methods. However, with advance in technology it has become relatively simple to analyse 2-way Fluid Solid Interactions with programs like ANSYS. This project aims to study the behaviour of reed valves under different conditions like rotation and varying inlet pressure and the resulting change in fluid flow.